Analysis of cracking mechanism of concrete galleries in a super high arch dam. (1st December 2021) - Wei, Pengcheng; Lin, Peng; Peng, Haoyang; Yang, Zongli; Qiao, Yu
Highlights: Gallery cracking mechanism is dominated by structural effects, loading, boundary conditions and material properties. A 3D anlysis method and geometry characteristics for dam gallery design is proposed. A cracking prevention and treatment procedure is proposed and verified by on-site monitoring. Abstract: It is essential to understand the cracking mechanism of dam galleries for the overall structural design and safety of a dam. In this study, the stress equation of the D-shaped concrete gallery is derived by the complex function method of elastic mechanics and the conformal mapping method. Based on a series of field tests, monitoring data, and three-dimensional (3D) nonlinear numerical simulation, the pattern and causes of cracks in the concrete gallery of a super high arch dam 15 m above the foundation are determined. The effects of the gallery structure, position, temperature, reservoir impoundment, curtain grouting and construction process on the tensile stress distribution and cracking risk at different stages are analyzed in detail. The gallery cracking mechanism is dominated by structural effects, loading, boundary conditions and material properties during the design, construction and operation periods. The corresponding prevention and treatment methods for cracking of concrete galleries are proposed. The 1/2 height-span catenary shaped (HSC-shaped) and smaller gallery at the downstream side with a distance to the foundation in the range of 10 to 15 m is recommended. The results in this study can provide some reference for the design and cracking prevention for dam galleries.